Implementation of the Minister of Transportation Regulation No. 24 of 2021 Policy for Service Improvement at Purabaya Terminal: Implementasi Kebijakan Peraturan Menteri Perhubungan No. 24 Tahun 2021 untuk Peningkatan Layanan di Terminal Purabaya - Oktaviani, Diana; Widiyarta, Agus (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
The purpose of this study was to examine in depth the implementation of the boarding pass system service policy at Purabaya Terminal. This study used a qualitative method and obtained the following results: (1) The standards and targets of the policy indicate that the division of passenger zones has complied with the Minister of Transportation Regulation No. 24 of 2021; (2) Resources have been implemented through adequate availability of staff, although a consistent attitude in realizing the boarding pass service system needs to be enforced; (3) The characteristics of the implementing organization are well-structured and scheduled; (4) Communication between organizations is not fully implemented as some bus company parties reject it; (5) The attitudes of the implementers overall demonstrate knowledge of the new system; (6) The socio-economic and political environment is able to implement the boarding pass system socially by meeting passengers’ security needs, economically by increasing company revenue, and politically by cooperating with government agencies. Therefore, the boarding pass system implementation has not been fully successful. To ensure the boarding pass system can run according to plan, BPTD Class II East Java is recommended to undertake several measures to improve public service transformation, such as: (1) Establishing a special organizational structure that is directly responsible for boarding pass system implementation; (2) Emphasizing the role of staff at Purabaya Terminal to provide more structured and consistent service according to the established schedule; and (3) Intensifying socialization efforts to bus companies to mandate the transition to the e-ticket system.